IMPLEMENTASI KURIKULUM MERDEKA DALAM PENINGKATAN KOMPETENSI SISWA (STUDI KASUS DI SD NEGERI BOJONGKADU, KABUPATEN CIANJUR) - Aries Rapelianto; Ai Nurhaeti; Elis Marsidah; Iim Wasliman; R.Supyan Sauri; Helmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Merdeka Curriculum has been implemented as a national curriculum reform to support flexible and student-centered learning. At the elementary school level, this curriculum is expected to enhance students’ competencies, including knowledge, skills, and attitudes. This study aims to describe the implementation of the Merdeka Curriculum and analyze its contribution to improving student competencies at SD Negeri Bojongkadu, Cianjur Regency. The study employed a qualitative approach with a case study design. The research subjects consisted of the school principal, classroom teachers, and students selected through purposive sampling. Data were collected through observations, interviews, and document analysis, and analyzed using an interactive data analysis model. The findings indicate that the Merdeka Curriculum has been implemented through flexible learning planning, student-centered instructional practices, and the application of diagnostic and formative assessments. This implementation contributes to the improvement of students’ competencies in terms of knowledge, skills, and attitudes. The study concludes that the Merdeka Curriculum supports holistic student competency development in elementary schools, although strengthening implementation consistency and continuous school support remain necessary. Keywords: Merdeka Curriculum, student competencies, elementary school, curriculum implementation, student-centered learning